Analisis Kinerja Keuangan Perusahaan Sebelum dan Setelah Implementasi PSAK 73 : (Studi pada Perusahaan Perhotelan dan Restoran di Bursa Efek Indonesia) - Annisa Papuanita Hefiria; Agrianti Komalasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyse the impact of the implementation of PSAK 73 which focuses on changes in key financial ratios, namely Debt to Equity, Return on Assets, and Return on Equity. The results showed that DER experienced a significant increase, ROA in the first year experienced a significant decrease and ROE experienced a significant decrease due to depreciation and rental interest. Overall, the implementation of PSAK 73 affects the company's financial structure, increases leverage, and decreases profitability and affects asset efficiency although not consistently. This study also responds to the importance of financial statement transparency with the recognition of right-to-use assets and lease liabilities that provide a more realistic picture of the company's liabilities and assets. This study suggests expanding the sample, considering other variables, and using more complex quantitative and qualitative analysis methods to gain a deeper understanding.